Social moral judgment among students that consume alcohol beverages: acceptability, categories of justification and authority jurisdiction - Cruz, Luciana Ap. Nogueira da; Martins, Raul Aragão; Teixeira, Patrícia Santos (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2009)
The knowledge about the use of alcohol and other drugs among adolescents and young people is well described in scientific literature, however, little is known about how this behavior is judged in socio moral terms. This research aims to assess how 46 high-school students in a city in the interior of the state of São Paulo, Brazil, judge the behavior of consumption of alcohol beverages (including drinking and driving), theft, aggression and crash helmet use. Results show that drinking and driving, aggression and theft are considered the least acceptable behaviors, and the use of alcohol beverages is classified in the conventional and prudence domains.